Social Ecology Model of Factors Influencing Leadership Ability of Graduates in Zhengzhou City - Peng, Ziqian; Khatibi, Ali; Tham, Jacquline (Journal of Theory and Practice in Education and Innovation, 2025)
This study aims to use social ecology theory to guide the role of graduates in enhancing leadership ability in higher education and the positive impact of social ecology on students' self-efficacy. This study adopts a quantitative research methodology and uses structural equation modelling AMOS to test the hypotheses. A questionnaire was administered to students in 86 colleges and universities in Zhengzhou City to obtain data on the students' leadership development in colleges and universities as well as in their own surroundings prior to graduation.